CSF cytokine, chemokine and injury biomarker profile of glial fibrillary acidic protein (GFAP) autoimmunity - Yahel Segal; Georgios Mangioris; Vanda Lennon; Binxia Yang; Divyanshu Dubey; Eoin P. Flanagan; Andrew McKeon; John R. Mills; Michel Toledano; Ivana Vodopivec; Sean J. Pittock; Anastasia Zekeridou (Annals of Clinical and Translational Neurology)
Abstract Defining the CSF cytokine/chemokine and injury biomarker signature of glial fibrillary acidic protein (GFAP) autoimmunity can inform immunopathogenesis. CSF GFAP‐IgG‐positive samples (N = 98) were tested for 17 cytokines/chemokines, neurofilament light chain (NfL), and GFAP (ELLA, Bio‐Techne). Controls included non‐inflammatory (N = 42), AQP4‐IgG‐positive (N = 83), CNS infections (N = 13), and neurosarcoidosis (N = 32). IL5, IL6, IL10, IL8/CXCL8, CXCL9, CXCL10, CXCL13, BAFF, GM‐CSF, IFN‐gamma, and TNF‐alpha concentrations were higher compared to non‐inflammatory controls (P < 0.01). GFAP concentrations were similar to those of AQP4‐IgG‐positive patients; NfL was higher (P < 0.001) and correlated with MRI changes and outcomes. CSF cytokine/chemokine findings in GFAP autoimmunity correlate with histopathology; GFAP and NfL hold promise as disease biomarkers.